Rozwiąż równania:

a) 3x = 9

b) 2x+4 = 6

c) 3x - 1 = 5

d) 9x - 3 = 2x + 5


Odpowiedź :

Odpowiedź:

a)

3x = 9 /: 3

x = 3

Sprawdzenie:

3 • 3 = 9

9 = 9

L = P

b)

2x + 4 = 6

2x = 6 - 4

2x = 2 /: 2

x = 1

Sprawdzenie:

2 • 1 + 4 = 6

2 + 4 = 6

6 = 6

L = P

c)

3x - 1 = 5

3x = 5 + 1

3x = 6 /: 3

x = 2

Sprawdzenie:

3 • 2 - 1 = 5

6 - 1 = 5

5 = 5

L = P

d)

9x - 3 = 2x + 5

9x - 2x = 5 + 3

7x = 8 /: 7

x = 8/7

x = 1 i 1/7

Sprawdzenie;

9 • 1 i 1/7 - 3 = 2 • 1 i 1/7 + 5

9 • 8/7 - 3 = 2 • 8/7 + 5

72/7 - 21/7 = 16/7 + 35/7

51/7 = 51/7

7 i 2/7 = 7 i 2/7

L = P